KEGAGALAN UNITED NATIONS COMMISSIONS FOR INDIA PAKISTAN (UNCIP) DALAM MENYELESAIKAN KONFLIK INDIA PAKISTAN PADA TAHUN 1948-1950 United Nations Commissions For India Pakistan (UNCIP) Failure In Resol - Dinni Anderista Rahadyani (HI 16 UMY 019, 2016)
*19 Abstract This article uses descriptive qualitative method, data collecting technique and also librariy research by means of books, journals, articles, internet, newspapers, etc. the purpose of this article is to describe the United Nations Commissions for India Pakistan (UNCIP) policy in solving the conflict in India and Pakistan. This analysis uses the theory of conflict resolution and organizational theory. Objects in this article are India and Pakistanis a country involved in the conflict, while the subject in UNCIP as a representatives of the UN to resolve the conflic in India Pakistan. But in this case UNCIP not successfully resolve conflict in India Pakistan because of constraints on the inside and outside UNCIP. So this article writes about the failure of UNCIP in resolving conflcts in India Pakistan.